Selected physical and chemical properties of an alkaline bog lake - (:unkn) unknown (My University, 1974)
Mud Lake is located in Ozaukee County, Wisconsin, on land adjoining the UW-Milwaukee Field Station. It is surrounded by Cedarburg Bog, the most extensive bog in southeastern Wisconsin. This lake is unusual among bog lakes in being alkaline. Some work has been done on the chemistry of acid bog lakes (Malins Smith, 1942; Gorham, 1956; Gorham and Pearsall, 1956; Hayward, 1957), but none of these authors sampled sites with pH values approximating those of Mud Lake. The primary purpose of this study was to begin a data bank of chemical analyses of Mud Lake water samples. The availability of such data should stimulate further research on this unique lake. During the summer of 1974, selected physical and chemical properties of this lake were studied. Briefly, this project entailed sampling at three major stations in the lake at intervals of approximately three weeks. Three other stations were sampled sporadically throughout the summer. One 24-hour diurnal study was also done. Samples from 0, .25, .5, .75, and .9 meters were analysed for pH, color, turbidity, alkalinity, dissolved oxygen, nitrogen and phosphorus. Surface temperature was measured and an accurate bathymetric map of Mud Lake was constructed.
Keywords: Mud Lake; Cedarburg Bog; alkaline lake